CLINICAL STUDY ON INCIDENCE OF DYSTOCIA IN BUFFALOES AT REFERRAL HOSPITAL–A RETROSPECTIVE STUDY - CHAUDHARY, B G; CHAUDHARI, C F; SUTARIA, T V; CHAUDHARI, R K; SUTHAR, B N; NAKHASHI, H C; DALSANIYA, U R (The Indian Journal of Animal Reproduction, 2022)
Buffaloes (n=152) suffered with dystocia and referred to Veterinary Clinical Complexwere included in the study to investigate various clinical findings of dystocia.Incidence of maternal dystocia (90.13%) was dominant over occurrence of fetal dystocia (9.87%) in buffaloes. Among maternal dystocia, uterine torsion was significantly (P=0.001) dominant cause with 83.94% cases followed by incomplete cervical dilation (16.06%). Frequencies of right side, post-cervical and >3600 uterine torsions were significantly(P=0.001) higher as compared to left side, pre-cervical and <3600 uterine torsions, respectively.Fetal mal-disposition contributed the main cause among fetal dystocia.